Association of Forward Head Posture and Hand Grip Strength Among Mobile Users - Riaz, Namra; Saeed, Warda; Shabir, Laraib; Nouman, Sehar; Haq, Kiran; Sheikh, Naseebullah; Batool, Shumaila; Noor Ul Eman (Indus Journal of Bioscience Research, 2024)
Objective: To determine the association between forward head posture (FHP) and hand grip strength among smartphone users. Methods: A cross-sectional study was conducted on 130 participants aged 18-30 years. Non-probability purposive sampling was used. Demographics (age, gender, daily smartphone usage) were recorded. Forward head posture was assessed using the craniovertebral angle (CVA) measured with a goniometer. Hand grip strength was evaluated using a handheld dynamometer with participants seated, the elbow flexed at 90°, and the forearm in neutral position. Pearson correlation was used to analyze the relationship between CVA and grip strength in SPSS version 25, with a p-value <0.05 considered significant. Results: The mean age of participants was 24.02±3.5424.02±3.54 years, with an average smartphone usage of 8.47±1.708.47±1.70 hours. The mean CVA was 36.92±2.8636.92±2.86 degrees, and the mean hand grip strength was 22.07±6.6622.07±6.66 kg. A significant positive correlation was found between CVA and hand grip strength (r=0.459, p=0.01r=0.459, p=0.01). Subgroup analysis showed stronger correlation in males (r=0.482r=0.482) than females (r=0.443r=0.443). Conclusion: FHP significantly affects hand grip strength, with prolonged smartphone use being a major contributor. Ergonomic interventions are needed to reduce musculoskeletal risks.